Efficient tuning of potential parameters for liquid–solid interactions. Issue 11 (23rd July 2016) - Isaiev, Mykola; Burian, Sergii; Bulavin, Leonid; Gradeck, Michel; Lemoine, Fabrice; Termentzidis, Konstantinos
Abstract: Spherical and cylindrical water droplets on silicon surface are studied to tune the silicon–oxygen interaction. We use molecular dynamics simulations to estimate the contact angle of two different shaped droplets. We found that the cylindrical droplets are independent of the line tension as their three phases curvature is equal zero. Additionally, we compare an analytical model, taking into account or not the Tolman length and we show that for spherical small size droplets, this length is important to be included, in contrast to cylindrical droplets in which the influence of the Tolman length is negligible. We demonstrate that the usual convenient way to exclude linear tension in the general case can give wrong results. Here, we consider cylindrical droplets, since their contact angle does not depend on the droplet size in the range of few to 10ths of nanometres. The droplets are stabilised due to the periodic boundary conditions. This allows us to propose a new parameterisation for nanoscale droplets, which is independent the size of the droplets or its shape, minimising at the same time the calculation procedure. With the proposed methodology, we can extract the epsilon parameter of the interaction potential between a liquid and a solid from the nanoscaled molecular simulation with only as input the macrosized experimental wetting angle for a given temperature.